SHARP POWER AND DIGITAL SURVEILLANCE: THE NEW COGNITIVE WAR (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
To the new forms of conflict taking place in the world correspond, or are linked, newforms of power: from cognitive warfare to sharp power, up to what is now called surveillancecapitalism. Through cognitive conflict and sharp power strategies, we are witnessing anepochal change, an IT revolution that brings political conflict into a digital dimension, whichacts on the ground of public opinion, politics and economics; but even more subtly it acts in thecontrol and conditioning of knowledge, of our world view and of facts. The general objective,from a political philosophy and communication ethics point of view, is to understand whatchanges are taking place and the purposes of controlling information, the conditioning ofknowledge, the power of world markets and economic forces, which can be destructive asweapons of war: they can affect the strength of moral and collective resistance of a people, thereputation of a head of state, can pollute information for the failure of diplomatic operations,etc. How can one find adequate tools for cognitive response, autonomy of judgment anddecision, exercise of freedom, protection of rights, in particular those of the most fragilesocial groups who are also the most affected by the new forms of power and unconventionalconflict? The aim of my work will be to analyze forms, methods and languages of thisinterweaving of knowledge conditioning, digital market control, power (political and social),and global competitiveness